2007
DOI: 10.1266/ggs.82.409
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis as revealed by mitochondrial transcript profiles during germination and early seedling growth in wheat

Abstract: Germination of imbibed embryos is the initial stage of plant development that is accompanied by the burst of mitochondrial respiration. To understand the process of mitochondrial biogenesis during this critical stage in wheat development, we monitored changes in mitochondrial transcript profiles during the first 3 days by adopting a newly devised macroarray system. The whole experiment was conducted in the dark to avoid influences of photosynthesis. Dry quiescent embryos started respiration rapidly after imbib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…4). A similar situation was found also under normal conditions (Khanam et al, 2007). With respect to another polycistronic unit of nad6-nad1 in wheat (Haouazine et al, 1993), nad6 transcript showed decreases by all three stresses but nad1 transcript decreased mainly by low temperature stress.…”
Section: Expression Dynamics Of Mitochondrial Transcripts Under Abiotsupporting
confidence: 79%
See 4 more Smart Citations
“…4). A similar situation was found also under normal conditions (Khanam et al, 2007). With respect to another polycistronic unit of nad6-nad1 in wheat (Haouazine et al, 1993), nad6 transcript showed decreases by all three stresses but nad1 transcript decreased mainly by low temperature stress.…”
Section: Expression Dynamics Of Mitochondrial Transcripts Under Abiotsupporting
confidence: 79%
“…low temperature, high salinity and high osmotic potential were applied to germinating embryos after imbibition and seedlings. Imbibition and sterilization of seeds were performed according to Khanam et al (2007). For low temperature stress, imbibed seeds were placed on filter paper containing 0.1% Hyponex (N-P-K = 5-10-5, Hyponex, Osaka, Japan) solution in the dark at 4°C for 1 to 3 days.…”
Section: Plant Materials and Experimental Conditionsmentioning
confidence: 99%
See 3 more Smart Citations